Combined Effects Of Aloe Vera And Manuka Honey On IL-6 Level In Periodontitis-Induced Rats - Isa Anshori Muchaeroni; Recita Indraswary; Anggun Feranisa; Rahmawati Sri Praptiningsih; Eko Hadianto; Irma Dewi Ratnawati; Nindi Rahmawati Santoso (Jurnal Medali, 2026)
ABSTRACTBackground: Periodontitis is a multifactorial inflammatory condition that progressively damages the tooth-supporting structures, including the alveolar bone and periodontal ligament. This process involves a rise in pro-inflammatory cytokines, such as IL-6, which are essential agents in the inflammation and tissue destruction. Aloe vera (Aloe vera) and manuka honey are recognized for their ability to reduce inflammation and suppress the release of pro-inflammatory signaling molecules, such as IL-6. This study aims to evaluate the effectiveness of the combination of Aloe vera and Manuka honey in reducing IL-6 level in periodontitis rats.Method: Thirty rats were randomly assigned to four experimental groups: a control group, Aloe vera group, Manuka Honey group, and a group receiving a combination of Aloe vera and Manuka Honey. The Aloe vera and Manuka Honey treatments were administered via a gingival injection at a dose of 150 uL. After five days treatment, the rats were euthanized. An ELISA (Enzyme-Linked Immunosorbent Assay) was  conducted on the gingival tissue to measure the concentration of Interleukin-6 (IL-6).Result: The combination of Manuka honey and Aloe Vera significantly reduced IL-6 levels compared to the control group (p=0.000).Conclusion: The combination of Aloe Vera and manuka honey are effectively and  significantly reduced on IL-6 level.